Engineering Good: How Engineering Metaphors Help us to Understand the Moral Life and Change Society. - Coeckelbergh, Mark (Science & Engineering Ethics, 2010)
Engineering can learn from ethics, but ethics can also learn from engineering. In this paper, I discuss what engineering metaphors can teach us about practical philosophy. Using metaphors such as calculation, performance, and open source, I articulate two opposing views of morality and politics: one that relies on images related to engineering as science and one that draws on images of engineering practice. I argue that the latter view and its metaphors provide a more adequate way to understand and guide the moral life. Responding to two problems of alienation and taking into account developments such as Fab Lab I then further explore the implications of this view for engineering and society.